Dampak Kebijakan Publik Dalam Program Penanggulangan Kemiskinan Di Kecamatan Alasa - Hulu, Dermawan N. K.; Hulu, Syukur Kasieli; Harefa, Amstrong; Harefa, Hendrikus O. N. (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine the impact of public policy in poverty alleviation programs in Alasa District. This study uses a descriptive approach with qualitative methods. Observation, interviews, and documentation are techniques for collecting data. This study was conducted in Alasa District, North Nias Regency. Based on the results of the study, it is concluded that: First, the impact of public policy in poverty alleviation programs in Alasa District has not been fully implemented, because many governments still misuse assistance or long-term dependence on social assistance. Second, the constraints of public policy in poverty alleviation programs in Alasa District are the limited budget and facilities in Alasa District, which hinder the implementation of the program. Third, efforts to overcome public policy constraints in poverty alleviation programs in Alasa District, namely the District Government in collaboration with the Regency Government so that the public policies provided run smoothly, always collecting and analyzing accurate and up-to-date data to facilitate more effective program planning and evaluation.